El estrés y su incidencia en la vida personal y laboral de las enfermeras del hospital Teófilo Dávila en el año 2013. - Dávila Guzmán, Mónica del Cisne (2014)
Stress is now one of the main silent health problems that exist in the global society, which affects both children, youth and seniors, professionals in which your job role is very responsible usually end up suffering from stress at some point of his life, which is presented as a problem that is multifactorial, involving social, occupational, personal, with an emphasis on behavioral and mental, which hinders their relationship with others and creates internal conflicts.